Spatially Heterogeneous Environmental Selection Strengthens Evolution of Reproductively Isolated Populations in a Dobzhansky–Muller System of Hybrid Incompatibility - Cushman, Samuel A.; Landguth, Erin L. (Frontiers in Genetics, 2016)
Within-species hybrid incompatibility can arise when combinations of alleles at more than one locus have low fitness but where possession of one of those alleles has little or no fitness consequence for the carriers. Limited dispersal with small numbers of mate potentials alone can lead to the evolution of clusters of reproductively isolated genotypes despite the absence of any geographical barriers or heterogeneous selection. In this paper, we explore how adding heterogeneous natural selection on the genotypes (e.g., gene environment associations) that are involved in reproductive incompatibility affects the frequency, size and duration of evolution of reproductively isolated clusters. We conducted a simulation experiment that varied landscape heterogeneity, dispersal ability and strength of selection in a continuously distributed population. In our simulations involving spatially heterogeneous selection, strong patterns of adjacency of mutually incompatible genotypes emerged such that these clusters were truly reproductively isolated from each other, with no reproductively compatible “bridge” individuals in the intervening landscape to allow gene flow between the clusters. This pattern was strong across levels of gene flow and strength of selection, suggesting that even relatively weak selection acting in the context of strong gene flow may produce reproductively isolated clusters that are large and persistent, enabling incipient speciation in a continuous population without geographic isolation.